An Examination of Quality of Work Life of Fitness Professionals - Ali Eraslan, (Journal of Educational Issues, 2024)
The aim of this study was to examine the quality of work life of fitness professionals. This study was applied to fitness professionals in health and fitness facilities in Ankara. A total of 194 voluntary fitness professionals (95 male and 99 female) were participated in the study. Data were collected through “Quality of Work Life Scale for Healthcare Personnel”. In the data analysis; descriptive statistics was used to investigate the frequency and percentage distribution of the participants’ demographic information. After the analysis of normality and homogeneity, T-Test and one-way analysis of variance (ANOVA tests were used to determine the differences in the quality of work life level. Tukey HSD test was used to determine the differences between groups. In the findings, significant differences were found between variables of age, gender, marital status, perceived personal income rate, work status, years in the sector and scores of the quality of work life of fitness professionals. The fitness professionals who were male, married, older, have high perceived income rate, work fulltime and freelance in the sector had higher scores of the quality of work life. As a result, some socio-demographic and working characteristics increase the quality of work life. The results of the research show that fitness professionals need to see their work as a part of their career, increase their perceived income level, have regular family life, and find enough time outside of work life in order to increase their work life quality.